Characterization of the Testis-Specific Angiotensin Converting Enzyme (tACE)-Interactome during Bovine Sperm Capacitation - Mina Ojaghi; Jacob Varghese; John P. Kastelic; Jacob C. Thundathil (Current Issues in Molecular Biology, 2022)
A comprehensive understanding of molecular and biochemical changes during sperm capacitation is critical to the success of assisted reproductive technologies. We reported involvement of the testis-specific isoform of Angiotensin Converting Enzyme (tACE) in bovine sperm capacitation. The objective of this study was to characterize the tACE interactome in fresh and heparin-capacitated bovine sperm through immunoprecipitation coupled with mass spectrometry. These interactions were validated by co-localization of tACE with beta-tubulin as an identified interactome constituent. Although interactions between tACE and several proteins remained unchanged in fresh and capacitated sperm, mitochondrial aldehyde dehydrogenase 2 (ALDH2), inactive serine/threonine protein-kinase 3 (VRK3), tubulin-beta-4B chain (TUBB4B), and tubulin-alpha-8 chain (TUBA8) were recruited during capacitation, with implications for cytoskeletal and membrane reorganization, vesicle-mediated transport, GTP-binding, and redox regulation. A proposed tACE interactional network with identified interactome constituents was generated. Despite tACE function being integral to capacitation, the relevance of interactions with its binding partners during capacitation and subsequent events leading to fertilization remains to be elucidated.